Central giant cell granuloma of the maxilla. (7th March 2013) - Gupta, Manish; Gupta, Monica; Singh, Sunder; Kaur, Rupinder
Abstract : Central giant cell granuloma (CGCG), formerly called giant cell reparative granuloma, is a non-neoplastic proliferative lesion of an unknown aetiology. It occurs most commonly in the mandible. The case reported here resembled a wide variety of conditions that led to a misdiagnosis both on clinical and radiographic examinations but was histopathologically diagnosed as CGCG. We managed this case by endoscopic excision and curettage via nasal route without producing external scar and avoiding damage to the un-erupted tooth.